Microstructure and Mechanical Properties of 06Cr13Ni4Mo Steel Treated by Quenching–Tempering–Partitioning Process. Issue 2 (February 2016) - Song, Yuanyuan; Cui, Jingping; Rong, Lijian
Abstract : A heat treatment process, quenching–tempering–partitioning (Q–T–P), has been applied to a low carbon martensitic stainless steel 06Cr13Ni4Mo. By using this process, ultrafine reversed austenite can be obtained at room temperature. The microstructures of the reversed austenite and the martensite matrix were characterized by transmission electron microscopy (TEM) and energy dispersive spectroscopy (EDS) in detail. The results show that the ultrafine reversed austenite is enriched in Ni resulting in the austenite stability at room temperature. Two new types of nano-scale carbide precipitates are found in the martensite matrix. Detailed analysis suggests that the two nano-scale precipitates can be identified as ω phase and λ phase carbides, respectively. The orientation relationship between the ω phase and matrix is [ 011 ] α / / [ 2 1 ¯ 1 ¯ 0 ] ω and ( 2 1 ¯ 1 ) α / / ( 01 1 ¯ 0 ) ω, while that between the λ phase precipitate and matrix is [ 011 ] α / / [ 0001 ] λ and ( 2 ¯ 00 ) α / / ( 1 2 ¯ 10 ) λ . For the present steel, the ultrafine reversed austenite and carbide precipitates obtained by Q–T–P treatment provide a good combination of high strength and toughness.